Plant Identity Shaped Rhizospheric Microbial Communities More Strongly Than Bacterial Bioaugmentation in Petroleum Hydrocarbon-Polluted Sediments - Dagher, Dimitri J.; de la Providencia, Ivan E.; Pitre, Frédéric E.; St-Arnaud, Marc; Hijri, Mohamed (Frontiers in Microbiology, 2019)
Manipulating the plant-root microbiota has the potential to reduce plant stress and promote their growth and production in harsh conditions. Community composition and activity of plant-roots microbiota can be either beneficial or deleterious to plant health. Shifting this equilibrium could then strongly affect plant productivity in anthropized areas. In this study, we tested whether repeated bioaugmentation with Proteobacteria influenced plant productivity and the microbial communities associated with the rhizosphere of four plant species growing in sediments contaminated with petroleum hydrocarbons. A mesocosm experiment was performed in randomized block design with two factors: 1) presence or absence of four plants species collected from a sedimentation basin of a former petrochemical plant, and 2) bioaugmentation or not with a bacterial consortium composed of ten isolates of Proteobacteria. Plants were grown in a greenhouse over four months. MiSeq amplicon sequencing, targeting the bacterial 16S rRNA gene and the fungal ITS, was used to assess microbial community structures of sediments from planted or unplanted microcosms. Our results showed that while bioaugmentation caused a significant shift in microbial communities, presence of plant and their species identity had a stronger influence on the structure of the microbiome in petroleum hydrocarbons contaminated sediments. The outcome of this study provides knowledge on the diversity and behavior of rhizosphere microbes associated with indigenous plants following repeated bioaugmentation, underlining the importance of plant selection in order to facilitate their efficient management, in order to accelerate processes of land reclamation.